Merenda and the jungle as an idyll loving space - Alvarado Vega, Óscar Gerardo (2022)
In this text we try to establish a close up between what Merenda represents and her name as the main idea in the novel, and in her relationship with Francis. The love story weaved between these two is the clear sign of what Miranda’s displacement represents as an equivalent subject from the jungle. She is the jungle, from here is confirmed her love relation with Francis, a double love, encounter with paradise, and the one with the beloved woman in a metaphoric fusion for him.